2015
DOI: 10.7439/ijbr.v6i10.2623
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study to Evaluate Transversus Abdominis Plane (TAP) Block in Abdominal Surgery by Total Requirement of Diclofenac as a Post Operative Analgesia drug

Abstract: Background: Transversus Abdominis Plane Block (TAPB) is a regional anesthesia technique. It provides analgesia after lower abdominal surgery particularly where parietal wall pain forms major component of pain. It allows sensory blockade of lower abdominal wall skin and muscles via local anesthetic deposition between Transversus Abdominis muscle and internal oblique muscle. We evaluated efficacy of unilateral TAPB with bupivacaine for postoperative analgesia in hernia repair in a hospital based, double blind, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The time of 1 st rescue analgesia requirement was 1140.66 ± 294.89 minute in TAP group and 210.33 ± 92.45 min in control group. 17 Another study by Cho et al compared US guided TAP block with standard pain management protocol in patients undergoing open appendectomy and reported significantly lower VAS score of 2 (1.5-3.2) in US guided TAP block in comparison to 5 (3.5-8) in control group at 30 minutes and 2 (1-2.8) in US guided TAP versus 4 (2.5-6) in control group after 24 hours of surgery. And reported that US guided TAP block is superior to conventional management of post-operative pain in patients undergoing open appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The time of 1 st rescue analgesia requirement was 1140.66 ± 294.89 minute in TAP group and 210.33 ± 92.45 min in control group. 17 Another study by Cho et al compared US guided TAP block with standard pain management protocol in patients undergoing open appendectomy and reported significantly lower VAS score of 2 (1.5-3.2) in US guided TAP block in comparison to 5 (3.5-8) in control group at 30 minutes and 2 (1-2.8) in US guided TAP versus 4 (2.5-6) in control group after 24 hours of surgery. And reported that US guided TAP block is superior to conventional management of post-operative pain in patients undergoing open appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used the landmark technique for performing TAP block as wider applicability and merit have been demonstrated by various previous research with the landmark technique. 28 The mid-axillary approach has paravertebral spread leading to blockade of lateral cutaneous afferents, contrary to Sono-anatomical clear ultrasound-guided anterior approach. 29 The neuro-fascial plane and its contents can act as an armory responsible for a prolonged duration of action in comparison to surgical incision, that is highly vascular and may lead to faster local anesthetic absorption and metabolism, which might explain the shorter duration of action in Group I in which 26.8% required analgesia within 4-6 hours as compared to Group T, where only 4.8% required analgesia within 4-6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…For reference purpose, we used study by Ila B. Patel et al . [ 6 ] MedCal statistical software was used for sample size calculation.…”
Section: Methodsmentioning
confidence: 99%